Formation of the Independent High Electoral Commission in accordance with Law No. (31) of the year 2019 - Abd Ali Hussein, Researcher. Hussein; Naeem khdair, Assist. Prof. Dr. saleem (Basra studies journal, 2024)
Democracy is not achieved merely by the act of voting on election day. Many dictatorial political systems around the world hold periodic elections, and sometimes the voter turnout in these elections exceeds that of established democratic countries. This is because representative democracy relies on two pillars: firstly, that elected representatives truly represent the people, and secondly, that these representatives work for the benefit of the people. These pillars cannot be realized unless elections are free and fair. The integrity of elections depends on the organization of the electoral process, its fair conduct, and supervision by an independent, neutral, and professional electoral authority. In Iraq, despite the transition from single-party rule to political and party pluralism, and despite the holding of periodic parliamentary elections after the US-British occupation of Iraq and the overthrow of the previous dictatorial regime on April 9, 2003, these elections did not produce true representatives of the Iraqi people. This can be attributed to various reasons, including legislative shortcomings in the law governing the Independent High Electoral Commission. Although the Iraqi legislature repealed the previous law governing the Independent High Electoral Commission, Law No. (11) of 2007, with the current Law No. (31) of 2019, and although this law addressed some of the deficiencies of its predecessor, it also suffered from shortcomings as it did not ensure the success of the commission in conducting free and fair elections due to its lack of necessary guarantees, particularly regarding the commission’s independence, neutrality, and professionalism. Therefore, the Iraqi legislature must address these gaps by amending Law No. (31) of 2019 governing the Independent High Electoral Commission to ensure the conduct of free and fair elections.